Quantification of Cooled Film Thermal Protection Using Net Heat Flux Reduction within Transonic Environments - Ligrani, P.; Knox, N. (Thermal engineering, 2025)
Considered are NHFR or net heat flux reduction data in order to illustrate and quantify turbulent thermal convection phenomena within a unique and intricate cooled film environment along the extremity end of a transonic turbine airfoil with a rim in the form of a squealer. Of particular focus are the consequences of modifying the magnitude of GAP (tip gap magnitude) which is adjacent to the outer end of the airfoil. Data are given for a variety of cooled film ratio of blowing conditions, as the coolant film is provided by two separate plenums that are connected to a row of holes which are located along the top segment of the concave surface of the blade, as well as to two dusting cooled film holes located on the end extremity of the blade. Line-averaged NHFR data show different dependence upon RoB u and RoB d ratios of blowing, depending upon the magnitude of GAP. Especially for the trailing edge portion of the squealer tip surface of the airfoil, NHFR data vary significantly with aft ratio of blowing RoB d for the 1.2 mm or smaller GAP arrangement, whereas very little variation with RoB d is present for the 2.0 mm or larger GAP environment. Here, GAP is the thickness of the flow gap at the blade tip. In addition, line-averaged NHFR data associated with the smaller GAP are often higher than values associated with the larger GAP, when compared for the same squealer surface airfoil tip locations, and at the same approximate RoB u and RoB d ratios of blowing. The flow and local static pressure variations within tip gap regions, which vary as the magnitude of GAP is changed, are less influential in regard to the data associated with the top portion of the concave surface of the two-dimensional airfoil. The impact of the present arrangements and configuration is new and unique NHFR results for different GAP values for complex boundary layer and separation flow environments, which are different from all other data which are available within the archival literature.